Peran Aktif Mahasiswa KPM STAIN Meulaboh dalam Pembuatan Plang Selamat Datang: Upaya Penguatan Identitas Lokal Gampong Lhok Bubon - Indah Zahra; Khairuddin Hasan; Musayyada; Vira Yunidar; Evi Susanti; Rezi Fahleva; Pretty Ferdiyanti; Waldi Fajar Ramadhan (Pusat Penelitian dan Pengabdian Kepada Masyarakat STAIN Teungku Dirundeng Meulaboh, 2025)
The Community Service Lecture (KPM) activity of STAIN Teungku Dirundeng Meulaboh in Gampong Lhok Bubon aims to strengthen local identity through the creation of a welcome sign that integrates local cultural values. Participatory methods are used by involving the community in the design, creation, and placement of the sign, as well as the mentoring program for the Al-Qur'an Education Park (TPQ) and social services. The result is the creation of a welcome sign that combines traditional Acehnese motifs, Islamic calligraphy, and local language, becoming a symbol of community pride. The high level of active participation of residents shows a sense of ownership of the program. In addition, the TPQ activity succeeded in increasing children's interest in learning, while the social service improved environmental cleanliness. Collaboration between students, lecturers, and the community proves that a culture-based approach can be an effective solution in preserving local identity amidst the challenges of globalization. This program not only strengthens local wisdom values, but also becomes a model of sustainable service for community development.